Lugdunin amplifies innate immune responses in the skin in synergy with host- and microbiota-derived factors - Katharina Bitschar (Nature Portfolio, 2019)
Lugdunin is a peptide antibiotic produced by the skin commensal Staphylococcus lugdunensis. Here, the authors show that lugdunin reduces Staphylococcus aureus colonization in human keratinocytes and mouse skin by inducing the expression of human LL-37 and recruitment of monocytes and neutrophils.